2022
DOI: 10.1155/2022/3807265
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Combination of Continuous Nursing Care and Breathing Exercises on Respiratory Function, Self‐Efficacy, and Sleep Disorders in Patients with Lung Cancer Discharged from Hospital

Abstract: The purpose of this study was to explore the effect of respiratory function and self-efficacy of patients with lung cancer after surgery by the combination of continuing nursing care and breathing exercises and to assess its clinical value in improving the quality of patients’ sleep. 120 cases of lung cancer patients were divided into the control group (n = 60 cases) and the experimental group (n = 60 cases) randomly. The control group used conventional care methods for postoperative lung cancer patients, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The present study found that health belief, respiratory exercise adherence can positively in uence rehabilitation self-e cacy [34,35],…”
Section: Discussionsupporting
confidence: 48%
“…The present study found that health belief, respiratory exercise adherence can positively in uence rehabilitation self-e cacy [34,35],…”
Section: Discussionsupporting
confidence: 48%
“…However, positive coping styles and SOC are not always helpful in alleviating trauma. Thus, patients with lung cancer undergoing chemotherapy may lose confidence in treatment and develop sadness and despair, which impacts the level of PCER 55. Therefore, among this group of patients, self-confidence should be developed while invoking the power of anticancer role models to foster PCER 56…”
Section: Discussionmentioning
confidence: 99%
“…Thus, patients with lung cancer undergoing chemotherapy may lose confidence in treatment and develop sadness and despair, which impacts the level of PCER. 55 Therefore, among this group of patients, self-confidence should be developed while invoking the power of anticancer role models to foster PCER. 56 Patients in the high-PCER group had moderate and high levels of SOC and PCER, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to suffering from symptoms associated with LC, such as pain, chemotherapy reactions, and sleep difficulties, LC patients also endure a Am J Cancer Res 2024;14(3):1278-1291 range of psychological and emotional distress, including anxiety, depression, despair, a sense of burden, and concerns about their families. These factors compromise both their physical and mental health, as well as their dignity and quality of life (QoL) [10,11]. Prior research has revealed that LC patients have a high demand for continuous care after operation, mainly involving environmental support, self-health management knowledge and skills, health improvement, and psychological support [12].…”
Section: Introductionmentioning
confidence: 99%